Global distribution of material inflows to in‐use stocks in 2011 and its implications for a circularity transition. (21st July 2021) - Aguilar‐Hernandez, Glenn A.; Deetman, Sebastiaan; Merciai, Stefano; Rodrigues, João F. D.; Tukker, Arnold
Abstract: Around 40% of global raw materials that are extracted every year accumulate as in‐use stocks in the form of buildings, infrastructure, transport equipment, and other durable goods. Material inflows to in‐use stocks are a key component in the circularity transition, since the reintegration of those materials back into the economy, at the end of the stock's life cycle, means that less extraction of raw materials is required. Thus, understanding the geographical, material, and sectoral distribution of material inflows to in‐use stocks globally is crucial for circular economy policies. Here we quantify the geographical, material, and sectoral distributions of material inflows to in‐use stocks of 43 countries and 5 rest‐of‐the‐world regions in 2011, using the global, multiregional hybrid units input–output database EXIOBASE v3.3. Among all regions considered, China shows the largest amount of material added to in‐use stocks in 2011 (around 46% of global material inflows to in‐use stocks), with a per capita value that is comparable to high income regions such as Europe and North America. In these latter regions, more than 90% of in‐use stock additions are comprised of non‐metallic minerals (e.g., concrete, brick/stone, asphalt, and aggregates) and steel. We discuss the importance of understanding the distribution and composition of materials accumulated in society for a circularity transition. We also argue that future research should integrate the geographical and material resolution of our results into dynamic stock‐flow models to determine when these materials will be available for recovery and recycling. This article met the requirements for a Gold‐Gold JIE data openness badge described in http://jie.click/badges